First record of Travunioidea (Arachnida: Opiliones: Laniatores) from China, with the description of a new monotypic genus from a cave - Zhang, Chao; Derkarabetian, Shahan (Zootaxa, 2021)
A new genus and species of troglobitic Opiliones, Sinonychia martensi gen. n. & sp. n., is described and illustrated. This is the first report of the superfamily Travunioidea Absolon & Kratochvíl, 1932 from China. The new species is assigned to Cladonychiidae Hadži, 1935 on the basis of morphology of midgut and male genitalia, and can be easily distinguished from related genera by several characters.